Use of Smartphone Applications to Augment Colonoscopy Preparation Instructions and Effect on Quality of Colonoscopy Preparation and Adenoma Detection Rate – : A Systematic Review and Meta-Analysis - Ghazaleh, Sami (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.